Proyecto de inversión para la creación de una operadora turística radicada en la ciudad de Guayaquil - Carvajal Cerón, Verónica Germania (2009)
The purpose of this project is to know the feasibility of realize an investment for the creation of a Tourist Operator settled in Guayaquil city as an new alternative in the tourist sector, that focuses in offering the necessary advertising to the great diversity of tourist attractions that has our country, getting to know it in a fun way, participative and traveling around doing not conventional routes. The market will be analyzed to which the service wants to be focused initially, as well as its financial projection and the plan of marketing in which the function of the business was evaluated like its operation and its relation with the environment. “Diviértette Ecuador” will carry out an investigation of market to know the acceptance that would have the service of a Tourist Operator with the characteristics mentioned above and for their expansion to international routes in the long term. Finally a financial analysis will be carried out in which the feasibility of the implementation of strategies for the establishment of the Tourist Operator in the city of Guayaquil. And in this way to offer them a more attractive image for Tourists National and International